Managing public policy in India: The implementation gap - Jain, R.B. (1997)
The author analyses the processes of policy formulation, development and implementation in India to show as to how various political and administrative institutions involved therein affect the domestic policy. While examining inter alia the role of bureaucracy in public policy development in India, he discusses various factors which, according to him, account for problems witnessed in the areas. He also suggests few measures to remedy the situation. - Reproduced
Keywords: Public policy - India; Public policy